INFLUENCE OF DYSMENORRHEA GYMNASTIC ON MENSTRUAL PAIN TO 8TH GRADE STUDENTS OF SMPN 2 SOOKO DISTRICT MOJOKERTO - Titiek Idayanti; Hartin Su'idah; Devi Kharismanda Haryanto; Surya Mustika Sari; Heppy Rina Mardiana; Vera Virgia (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Light exercises (gymnastics) are highly recommended to reduce dysmenorrhea but during this adolescent only use medical therapy drugs to reduce the pain felt. The purpose of this study to determine the effect of dismal gymnastics on menstrual pain in adolescent girls 8th grade of SMPN 2 Sooko Mojokerto regency. The research design is Pre-Experimental Design with Static Group Comparison approach. The research variables are dysmenorrhea gymnastic as independent variable and dysmenorrhea pain as the dependent variable. The study population is all students of 8th grade who experienced menstrual pain in SMPN 2 Sooko as many as 54 people. A sample of 48 students taken with cluster sampling technique. Data were collected with pain scale observation sheets, and the results were tested with the Wilcoxon test. The results of Wilcoxon test showed that there was the influence of discharging gymnastics on menstrual pain in 8th grade of SMPN 2 Sooko Mojokerto. which is indicated by Ï = 0,000 and Î± = 0,05 so that Ï <Î± then H0 is rejected and H1 is accepted. Gymnastics dysmenorrhea with several movements that can provide a sense of comfort and calm so that it can affect the response of pain experienced by respondents. Students are expected to apply dysmenorrhea gymnastics to be able to relieve the pain of dysmenorrhea pain experienced so that the pain experienced can be reduced and respondents not only rely on pharmacological drugs in reducing the pain experienced.